SYNTHESIS OF VISCOELASTIC MATERIAL MODELS (SCHEMES) - Bogomolov, V.; Raznitsyn, I.; Bogomolov, S.; Богомолов, В. А.; Разницын, И. Л.; Богомолов, С. В.; Богомолов, В. О.; Разніцин, І. Л. (Харьковский национальный автомобильно-дорожный университет, 2014)
The principles of structural viscoelastic schemes construction for materials with linear viscoelastic properties in accordance with the given experimental data on creep tests are analyzed. It is shown that there can be only four types of materials with linear visco-elastic properties.
СИНТЕЗ ВЯЗКОУПРУГИХ МОДЕЛЕЙ (СХЕМ) МАТЕРИАЛОВ
СИНТЕЗ В’ЯЗКОПРУЖНИХ МОДЕЛЕЙ (СХЕМ) МАТЕРІАЛІВ
Keywords: viscoelastic model; structural scheme; Hooke element; Newton element; Maxwell model; Kelvin model; вязкоупругая модель; структурная схема; звено Гука; звено Ньютона; модель Максвелла; модель Кельвина; в’язкопружна модель; структурна схема; ланка Гука; ланка Ньютона; модель Максвелла; модель Кельвіна; 539.5 = 111